Identification and characterization of novel SCR7‐based small‐molecule inhibitor of DNA end‐joining, SCR130 and its relevance in cancer therapeutics. Issue 6 (18th March 2020) - Ray, Ujjayinee; Raul, Sanjay Kumar; Gopinatha, Vindya K.; Ghosh, Dipayan; Rangappa, Kanchugarakoppal S.; Mantelingu, Kempegowda; Raghavan, Sathees C.
Abstract: Targeting DNA repair with small‐molecule inhibitors is an attractive strategy for cancer therapy. Majority of DNA double‐strand breaks in mammalian cells are repaired through nonhomologous end‐joining (NHEJ). It has been shown that small‐molecule inhibitors of NHEJ can block efficient repair inside cancer cells, leading to cell death. Previously, we have reported that SCR7, an inhibitor of NHEJ can induce tumor regression in mice. Later studies have shown that different forms of SCR7 can inhibit DNA end‐joining in Ligase IV‐dependent manner. Recently, we have derivatized SCR7 by introducing spiro ring into core structure. Here, we report the identification of a novel inhibitor of NHEJ, named SCR130 with 20‐fold higher efficacy in inducing cytotoxicity in cancer cell lines. SCR130 inhibited DNA end‐joining catalyzed by rat tissue extract. Specificity analysis revealed that while SCR130 was specific to Ligase IV, it showed minimal or no effect on Ligase III and Ligase I mediated joining. Importantly, SCR130 exhibited the least cytotoxicity in Ligase IV‐null cell line as compared with wild type, confirming Ligase IV‐specificity. Furthermore, we demonstrate that SCR130 can potentiate the effect of radiation in cancer cells when used in combination with γ‐radiation. Various cellular assays in conjunction with Western blot analysis revealed that treatment with SCR130 led to loss of mitochondrial membrane potential leading to cell death by activating both intrinsic and extrinsic pathways of apoptosis. Thus, we describe a novel inhibitor of NHEJ with higher efficacy and may have the potential to be developed as cancer therapeutic.